Design and development of a 2 Degree of Freedom 3D Printed Myoelectric Prosthetic Arm to Sustain High Load for Amputees - Muhammad Izzat Nor, Ma'arof; Sunder Raj, Sundara Murthy; Choo, Wou Onn; Girma, Tadesse Chala (INTI International University, 2019)
In our fast-moving world, the advancement in 3D printed myoelectric prosthetic arm has been growing rapidly in the field of rehabilitation engineering. Prosthetic wrist needs to be small and compact minimizing the space taken. There are few designs developed by other developers around the globe; however, the designs have issues such as its degree of freedom and ability to handle high load without failing. Available 3D printed prosthetic hand wrist can rotate the hand along x-axis, however movement of up and down along the y-axis has not been practically researched and developed thoroughly. The main objective of this work was to design and develop a 3D printed 2 degree of freedom wrist joint for a 3D printed myoelectric prosthetic hand which can handle load of up to 10kg. The wrist joint design was done in AutoCAD where it will be made available to public for their development of 3D printed prosthetic hand and modifications. The design connects the palm and the forearm of the 3D printed myoelectric prosthetic arm. This wrist has 2 servos where one rotates about the x-axis and another rotates about the z-axis. Furthermore, the tendons that move the fingers was carefully designed to minimize the tension when the wrist moves along the x-axis and y-axis rotation. This design was developed to be made reliable and easy to assemble. The lifting capability was tested and compared with the available 3D printed prosthetic designs. The prosthetic hand was successfully developed with the new wrist design that can handle load up to 98.1N. As the fingers could not handle load higher than 800g each, the weight was lifted at its palm section connecting to the new wrist design.